Efektivitas Asas Presumptio Iures De Iure bagi Pelaku Anak Persetubuhan dengan Bujuk Rayu di Kota Batam - Tri Yanuarty Sembiring; Junimart Girsang; Rina Shahriyani Shahrullah (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2023)
Children are the next generation of the nation who have the right to live a decent life and achieve a bright future. However, there are still many children in Batam City who are involved in the criminal act, including of sexual intercourse with other children under mutual will, so that in the end the child perpetrators must end up in prison. This study aims to find a solution so that the Principle of Presumptio Iures de Iure for Child Offenders having sexual intercourse with persuasion can be applied effectively. The argument is based on the fact that the child perpetrators often claims that they do not know their actions were classified as a crime which regulated in Article 81 paragraph (2) of the Child Protection Act. However, our country's law adheres to the Principle of Presumptio Iures De Iure, which means that everyone is considered to know the law without exception, so that one cannot avoid the rule of law by arguing that he/she does not aware of it. The research method used this study is Sociological Empirical. The research results show, First, the principle of presumption iures de iure on Article 81 Paragraph (2) of the Child Protection Act is not implemented effectively in Batam City. Second, the obstacle that causes ineffective implementation of this principle is the public's ignorance of the existence of this article. Third, the solution in order to implement this principle effectively is to carry out socialization and legal counseling to the community by the government intensively, especially to young people in Batam City.